The Phaseolus vulgaris L. Yellow Bean Collection: genetic diversity and characterization for cooking time - Sadohara, Rie; Izquierdo, Paulo; Couto Alves, Filipe; Porch, Timothy; Beaver, James; Urrea, Carlos A.; Cichy, Karen (Genetic Resources and Crop Evolution, 2022)
Common bean (Phaseolus vulgaris L.) is a nutrient-rich food, but its long cooking times hinder its wider utilization. The Yellow Bean Collection (YBC) was assembled with 295 genotypes from global sources to assess the genetic and phenotypic diversity for end-use quality traits in yellow beans. The panel was genotyped with over 2,000 SNPs identified via Genotyping-By-Sequencing (GBS). Through population structure analyses with the GBS markers, the YBC was determined to be 69% Andean, 26% Middle American, and 5% admixture. The YBC was grown in two major bean production regions in the U.S., Michigan (MI) and Nebraska (NE) over two years. The genotypes exhibited a wide diversity in days to flower, seed weight, water uptake, and cooking time. The cooking times of the YBC ranged from 17–123 min. The cooking time were longer and varied more widely in NE with many more genotypes exhibiting hardshell than in MI. Fast-cooking genotypes were identified with various yellow colors; 20 genotypes cooked within 20 min in MI, and eight genotypes cooked within 31 min in NE. Water uptake and cooking time were significantly affected by the environment, which included both the growing and cooking environment, and notably in relation to cooking, NE is higher elevation than MI. SNPs associated with cooking time were identified with genome-wide association analyses and a polygalacturonase gene on Pv04 was considered to be a candidate gene. The genotypic and phenotypic variability, fast-cooking genotypes, and the associated SNPs of the YBC will lay the foundation for utilizing yellow beans for breeding and genetic analyses.